Biological invasion by Acacia spp. in the Brazilian Atlantic Forest - Heringer, Gustavo (2018)
Climate change, habitat degradation, and biological invasion are among the most factors threaten biodiversity. These factors, besides affect biodiversity and ecosystem directly, can act synergistically and promote deeper environmental changes. Therefore, in this thesis, we proposed to study the causes and consequences of biological invasion by Acacia genus. In the first chapter, we investigate the effects of biological invasion by Acacia spp., fire and eucalyptus disturbance, and land-use on a neglected sandy-savanna ecosystem named Mussununga; in the second, we tested the effects of landscape functioning and structure in the Acacia invasion in Mussununga ecosystem; and finally, assessed the potential distribution of Acacia mangium and A. auriculiformis in five climate scenarios and the potential effects in restoration programs. We found in the first chapter that Acacia promoted changes in the structure and phytophysiognomie of the woody layer, but did not affect the herb-shrub layer. On the other hand, anthropogenic factors affected both woody and herb-shrub layer. In the second chapter, we found that in a fragmented landscape with the higher road network, Mussununga has a higher chance to be invaded by Acacia. Shape index had a negative effect in Acacia invasion, while the length of roads, Mussununga size, Mussununga perimeter, length of highways and landscape conductance had a positive effect. Finally, in the third chapter, we found A. mangium has a large suitable area in all scenarios, while A auriculiformis is confined to a relatively small region of 13,083 km 2 (± 3.39 SD). In the low greenhouse gas emissions scenario (RCP 2.6), the suitable area for A. mangium expanded from the current scenario of 18.4% of the Atlantic Forest to 24.0% in the year 2050, while, achieved around 44,3% of the Atlantic Forest area in the worse scenarios (RCP 8.2, in 2070). Still in the scenarios with higher climatic change, the suitable area for A. mangium overlapped around 39.3% of the potential area for restoration programs, in Atlantic Forest.